Correlation between Working Memory Capacity with Anatomy Point of Medical Studies Program in Faculty of Medicine Sebelas Maret University - Rifqi Hadyan; Nanang Wiyono; Dian Nugroho (Nexus Pendidikan Kedokteran dan Kesehatan, 2015)
Background: Anatomy is one of the basic field of study in faculty of medicine (basic medical sciences), who will become the basic of clinical studies. Anatomy learning process influenced by working memory capacity. Working memory have a very important effect in human mental development including cognitive ability, the ability of human to plan something, to find solution, and to understand new things. Working memory is one of the cognitive ability that influence the study achievement. Methods: This study was an observational analytic study with cross sectional approach thar held at October, 6th, 2014 at Faculty of Medicine Sebelas Maret University with 61 respondents of third semester . The sampling was done by random sampling technique. The selection of sample done by checking the inclusion and exclusion criteria of this study sample. The amount of ample obtained statistically analyzed by using Pearson correlation test. Result: The result of Pearson correlation test was found that there were a significant correlation between working memory capacity with Anatomy Point of Medical Studies Program Third Semester Student in Faculty of Medicine Sebelas Maret University (p = 0.000) and the correlation between variables were moderate (r = 0.600) with positive direction of correlation. Conclusion: The correlation between working memory capacity and Anatomy Point of Medical Studies Program Faculty of Medicine Sebelas Maret University is significant. Keywords: Working Memory Capacity, Anatomy Point